Pollen micromorphology of four taxa of Anemone coronaria L. from western Turkey - Candan, Feyza; Çali, Ilkay Öztürk (Bangladesh Journal of Botany, 2015)
The present study examined a comparison of the pollen micromorphology of four taxa of Anemone coronaria L. (A. coronaria var. coccinea (Jord.)) Burn, A. coronaria var. rosea (Hanry) Batt, A. coronaria var. cyanea, A. coronaria var. alba Goaty & Pens) naturally distributed in western Turkey and its commercial cultivars of de Cean group. Measurements of pore width-length and exine-intine layer thicknesses were made using a micrometric ocular. In this study pore width-length and exine-intine layer thicknesses were found as decreased in all Anemone coronaria L. cultivars of de Cean group in respect to the varieties. The reasons for this variation could be the use of pesticides and tetraploid F1 hybrids of Anemone coronaria L. cultivars of de Caen group by the producers. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22720 Bangladesh J. Bot. 44(1): 31-36, 2015 (March)